Assessment of quality of life of ASHA workers using WHOQoL-BREF questionnaire - Bullappa, Asha; Kengnal, Prakash (International Journal Of Community Medicine And Public Health, 2017)
Background: ASHA represents a vital role in the strategy of NRHM. There is scarcity of information on quality of life and factors influencing it on ASHA workers. The assessment of quality of life in this group may help to better understand and develop an insight for measures that can be improved in their lives. The objective of the study was to assess the quality of life among ASHA workers of Mangalore and Udupi taluk, Karnataka. Methods: This is a questionnaire based, cross sectional study conducted for a period of 3 months (June 2015 - Aug 2015) on ASHA workers of Mangalore and Udupi Taluk, Karnataka. Local language Kannada version of WHO QoL BREF questionnaire consisting of 26 questions was used. Results: The mean age of ASHA workers across the study group was 42.40 years. With respect to perception of QoL and health, around 60% felt their quality of life (QoL) was good and health was satisfactory. Maximum and minimum mean scores was observed for self-esteem and financial resources respectively. Among the various domains of QoL, the ASHA workers had higher mean score in social domain, followed by physical, psychological and environmental. Conclusions: The ASHA workers had higher mean score in social domain, followed by physical, psychological and environmental.